2014
DOI: 10.1073/pnas.1316594111
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in prefrontal intrinsic connectivity

Abstract: The prefrontal cortex continues to mature after puberty and into early adulthood, mirroring the time course of maturation of cognitive abilities. However, the way in which prefrontal activity changes during peri-and postpubertal cortical maturation is largely unknown. To address this question, we evaluated the developmental stage of peripubertal rhesus monkeys with a series of morphometric, hormonal, and radiographic measures, and conducted behavioral and neurophysiological tests as the monkeys performed worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…These data are consistent with electrophysiological data from young and adult macaque monkeys, where it was found that adult monkeys had stronger functional connectivity within prefrontal areas and a higher firing rate during performance of a WM task [26] (Figure 2A,B).…”
Section: Connectivity and Capacity In Wm Developmentsupporting
confidence: 90%
See 2 more Smart Citations
“…These data are consistent with electrophysiological data from young and adult macaque monkeys, where it was found that adult monkeys had stronger functional connectivity within prefrontal areas and a higher firing rate during performance of a WM task [26] (Figure 2A,B).…”
Section: Connectivity and Capacity In Wm Developmentsupporting
confidence: 90%
“…In summary, evidence from electrophysiology, computational science, TMS, and neuroimaging together suggests that higher WM capacity is associated with [26]. (B) Differences in connectivity and frequency in young and adult macaque monkeys [26].…”
Section: Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we capitalized on this approach to investigate a relatively unexplored aspect of prefrontal cortical function, its developmental maturation. In a series of recent studies, we have addressed for the first time the nature of changes that the prefrontal cortex undergoes between the time of puberty and adulthood [25][26][27]41 . These studies revealed a number of changes in activity between young and adult subjects, however the significance of changes at some task epochs relative to others and their relationship to behavior has been difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Changing patterns of prefrontal activation between childhood and adulthood have been well documented in human imaging studies for tasks that require working memory [16][17][18][19][20][21][22] and response inhibition 5,19,21,23,24 . Recordings from single neurons in these tasks have been recently obtained in non-human primate models, at different developmental stages [25][26][27] . Monkey maturation of working memory and response inhibition parallels that of humans 28 .…”
Section: Introductionmentioning
confidence: 99%